The Snow Spider - "Nimo, Jenny" (Egmont: London, 2004)
In this exciting fantasy adventure Gwyn's grandmother decides to find out if Gwyn is a magician and gives him five strange birthday gifts. So begins an extraordinary story of triumph of love and loyalty over evil and hatred
Keywords: Fantasy fiction